2021
DOI: 10.1177/1557085120987613
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Dynamics Associated With Dating Violence Among Adolescents and Young Adults: A Feminist Post-Structural Analysis

Abstract: We focus on the character of adolescent and young adult relationships, and argue that attention to interpersonal features of intimate partner violence (IPV) is necessary for a comprehensive view of this form of violence. Drawing on ideas from feminist post-structural perspectives, we highlight studies that develop a somewhat non-traditional but nevertheless gendered portrait of relationships as a backdrop for exploring dyadic processes associated with IPV. Findings are based on quantitative and qualitative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Several studies relying on the TARS data have shown that cheating (not merely jealousy, as in traditional accounts) is associated with high levels of conflict within romantic relationships, including physical IPV (Giordano et al., 2015 ). Further, a more recent analysis indicates that while either or both partners’ cheating is associated with IPV, men's infidelity is more strongly related to physical violence (as evidenced by male as well as female respondents’ reports), at least within the context of this general population sample (Giordano et al., 2021 ).…”
Section: The Nature and Sequencing Of Cognitive Transformationsmentioning
confidence: 83%
“…Several studies relying on the TARS data have shown that cheating (not merely jealousy, as in traditional accounts) is associated with high levels of conflict within romantic relationships, including physical IPV (Giordano et al., 2015 ). Further, a more recent analysis indicates that while either or both partners’ cheating is associated with IPV, men's infidelity is more strongly related to physical violence (as evidenced by male as well as female respondents’ reports), at least within the context of this general population sample (Giordano et al., 2021 ).…”
Section: The Nature and Sequencing Of Cognitive Transformationsmentioning
confidence: 83%
“…Thus, as they gain more relationship experience, the idea of control has an active and grounded quality as it reflects each partner’s attempts to influence or change the other. This more localized focus on control dynamics inevitably connects to specific issues of concern and, at times, dispute that have the potential to further illuminate gender dynamics within early dating relationships (Giordano et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The political intensity the middle sister's community goes through places on each and every one of its inhabitants' dire psychological trauma and coercion, which altogether results in unnatural secrecy, covert and deliberate suppression, macabre rumors, augmented gender stereotyping, trespassing gossips, and frightening musings in scores of shapes and forms (Hutton, 2019;Danaci, 2020;Farrell, 2020). Giordano et al (2021) argue that power lies at the center of all sorts of feminist discourses that dichotomize between gender sides, relationship dimensions, and partners, orienting the comparatively vulnerable one, if not mechanically stigmatizing the less loud one as vulnerable, at the weaker corner to be dominated and to be a master of. The middle sister narrates her lived experiences through an unusual blend of lexicon discernibly suggesting her temperament, caution, and revenge against the entire social abnormalities (Hutton, 2019).…”
Section: Introductionmentioning
confidence: 99%